Brief Reflections on authoritarian Neoliberalism - Brindisi, Gianvito (Soft Power, 2024)
If, as is true, one of the thorniest issues within the debate on neoliberalism is the role played by law and the state, then the book by Orsetta Giolo (2020) is to be favourably welcomed as it represents a useful contribution to the construction of a clearer framework on this problem that has indefinite boundaries. Among the numerous opportunities for reflection offered by the text, it is certainly worth dwelling on the phenomenon that Giolo (2020) appropriately defines neoliberal binarism, that is, the reticular and authoritarian character of neoliberal law, corresponding to two different legal environments inhabited by different subjects: the first one is represented by governance and the metaphor of the network, aimed at promoting freedom and optimizing competition; the second one is represented by penal state, aimed at the annihilation of political agency and the exclusion of subjects that are not adjusted to neoliberal standards (p. 24).